Privacy in Big Data psychiatric and behavioural research: A multiple-case study. (September 2018) - Mostert, M.; Koomen, B.M.; van Delden, J.J.M.; Bredenoord, A.L.
Abstract: In Big Data health research, concerns have risen about privacy and data protection. While the ethical and legal discussion about these issues is ongoing, so is research practice. The aim of this qualitative case study is to gain more insight into how these concerns are currently dealt with in practice. For this multiple-case study, the YOUth cohort, a longitudinal cohort focusing on psychosocial development, and Big Data Psychiatry, a pilot study in Big Data analytics on psychiatric health data, were selected. A broad range of relevant documents were collected and semi-structured interviews with stakeholders were conducted. Data were coded, studied and divided into themes during an iterative analytical process. Three themes emerged: abandoning anonymisation, reconfiguring participant control, and the search for guidance and expertise. Overall, the findings show that it takes considerable effort to take privacy and data protection norms into account in a Big Data health research initiative, especially when individual participant level data need to be linked or enriched. By embracing the complexity of the law in an early phase, setbacks could be prevented, the existing flexibility within the law could be utilised, and systems or organisations could be designed and constructed to take relevant rules into account. Our paper illustrates that a close collaboration of experts with different backgrounds within the initiative may be necessary to be able to successfully navigate this process.